PENERAPAN METODE BERCERITA MEDIA DAN BONEKA WAYANG DALAM MENINGKATKAN KEMAMPUAN BAHASA LISAN - Jaya, Ilham; Fauziah, Anik (Jurnal Anak Bangsa, 2025)
Language development is one aspect of early childhood development that must be stimulated. Children between three and four years old can speak, listen, read and write. Aspects of the development of other fields depend heavily on language development. The aim of this research is to use wayang puppets to improve oral language skills through storytelling activities. The subjects of the research were 10 children consisting of 4 girls and 6 boys. This research is a two-cycle classroom action research carried out in four stages, namely planning, action, observation and reflection. Based on research results, telling stories with wayang puppets can help children develop oral language skills. In cycle I, children's oral language abilities were 60.1%. Cycle I continues to Cycle II because it has not reached the KKM value ≥ 75%. After researchers carried out improvement activities in cycle II, the percentage of children with very well developed oral language skills grew by 91.7%. Based on these results, it can be concluded that storytelling activities using wayang puppets can improve the oral language skills.